Rehabilitation of a Patient with Partial Maxillectomy: A Case Report - Ouaalla, Meriem; El Assraoui, Khadija; Zeroual, Rajae; Bellemkhannate, Samira (Integrative Journal of Medical Sciences, 2021)
The loss of maxillary bone is accompanied by severe functional, aesthetic, psychological, and social problems. The maxillofacial obturator prosthesis remains a therapeutic tool that improves aesthetics and restores the functions of chewing, swallowing, and phonation. A close collaboration between the maxillofacial surgeon and the dentist is essential to obtain an optimal prosthesis both functionally and aesthetically, thus allowing a socio-professional reintegration of the patient. There are three stages to rehabilitating a maxillary defect and a partially edentulous patient. First, an immediate obturator prosthesis is realized, then the secondary obturator prosthesis accompanies the healing process, and finally, the definitive obturator prosthesis is achieved. This article is a clinical report of different steps to fabricate a partial denture with an obturator in a partially edentulous patient with a maxillary defect.